The Qur'an for All: A Historical Analysis of Bengali Translations and Tafsir - Al Kausar, Aflatun (Universitas Muhammadiyah Surakarta, 2025)
This study explores the historical evolution of translating the meanings of the Holy Qur'an into the Bengali language. It delves into the methods and challenges faced in this translation process, highlighting the significance and impact of making religious texts accessible to a wider audience in Bangladesh. Through a historical analysis of the different translation stages, from the early 19th century to the present day, this research emphasizes the role of Bengali translations in shaping Islamic understanding and Tafsir among Bengali-speaking Muslims. The findings shed light on how these translations have influenced religious practices and promoted a deeper understanding of Islam in Bangladesh, while also identifying the need for continued efforts to ensure accuracy and faithfulness to the original Arabic text.